Baseline assessment of the physical and chemical properties of five sites in Miagao, Iloilo for onion (allium cepa L.) cultivation. - Olegario, Marielle Orolfo
Due to the sudden decrease in the yield of onion in 2012, the compatibility of the onion and non-onion cultivation areas in Miagao were assessed. Soil samples acquired from onion plantations of Barangay Bagumbayan and Barangay Durog as well as the non-onion growing sites of Barangay Oyungan and the University of the PhilippinesVisayas, were tested for their macro and microelemental content. The physical properties of the soil samples were also evaluated for their suitability for onion cultivation based on the recommended values provided by the University of Minnesota Extension Service., The following analyses were carried out: cation exchange capacity, soil organic matter, pH values, content of macronutrients (N, P, K, Ca, and Mg) and microelements (Cu, Zn, Fe, Na and Mn). Soil samples from Barangays Bagumbayan, Durog and Oyungan had the appropriate soil texture needed by onion. All of the sampling sites had standard content of sulfate, excess of copper, and deficient in nitrogen, organic matter, sodium and zinc. Aside from Barangay Oyungan, all the other samples are deficient in exchangeable potassium. Among the samples, only UPI had the ideal pH and adequate calcium for growing onion. These chemical analyses are useful in fertilization programs designed to optimize the quantitative and qualitative yields of onion production and to protect the soil environment in production farms.